(untitled) (Medical Forum Monthly, 2021)
Objective: Wound healing is a widely studied subject, and efforts are being made worldwide to make wound healing more effective. We carried out a study to assess the anti-inflammatory role of low level laser therapy and zinc oxide in wound repair. Study Design: Random sampling technique study Place and Duration of Study: This study was conducted at the Karachi Campus of Isra University. The study was carried out for duration of 6 months, from June 2020 till December 2020. Materials and Methods: 18 Albino rats were selected through random sampling and divided into three groups. Each group was given a normal daily diet along. An equal incision was made into all the rats of the group of the same size. Intervention was then carried out in which Group A received topical saline solution hence acting as the control group, Group B was given Low Level Laser Therapy (LLLT), and Group C was given Zinc Oxide topically. Histological tissue was attained on the 3rd and 7th day for analysis. Data was analyzed using SPSS with one-way ANOVA followed by post-Hoc tukeys test being applied. Results: Reduction in the Neutrophil and Lymphocyte count was seen in Group B (Day 3: 19.65±2.30, Day 7: 8.55±5.1) and Group C (Day 3:23.00±8.30, Day 7: 18.44±3.34), however Group B in which LLLT was the interventional agent demonstrated the most favorable result. Significant difference was obtained when comparing group B to A on day 3 (<0.01) and 7 (<0.001), as well as when Group B was compared to Group A on day 3 (0.01) and day 7 (<0.001). Conclusion: Our study concludes that both LLLT and Zinc Oxide improve wound healing through their anti-inflammatory actions; however, LLLT showed more favorable results.